Performance of urinary liver-type fatty acid-binding protein in diabetic nephropathy: A meta-analysis - Zhang, Li; Xue, Shuai; Wu, Meiyan; Dong, Dan (Frontiers in Medicine, 2022)
Background.Diabetic nephropathy (DN) is one of the main causes of chronic kidney disease (CKD), which increases the risk of cardiovascular diseases and progresses to end-stage renal failure. Thus, early diagnostic markers for diabetic patients are urgently needed to improve the prognosis of DN and predict DN progression. Materials and Methods. PubMed, MEDLINE, and EMBASE were searched for publications until February 24, 2021, without any language limits. Review Manager 5.4 software was used for meta-analysis. Continuous data were obtained by calculating the standardized mean differences (SMDs) with 95% confidence intervals (CIs) if different scales were applied. We performed the heterogeneity test using the I2 statistic: P<0.1 and I2>50% meant statistical significance. Results. We included 13 studies with a total of 5605 participants. The uL-FABP concentrations in the normal albuminuria group were significantly higher than those in the normal control group without DM [P=0.009, SMD 1.72, 95% CI (0.44, 2.99)]. Urinary F-LABP levels were elevated in the macroalbuminuria group compared with those in the microalbuminuria group with DM [P=0.002, SMD 2.82, 95% CI (1.03, 4.61)]. Urinary L-FABP levels were also significantly increased in the progression and CKD groups compared with non-progression and CKD subjects with DM [P=0.02, P<0.00001, respectively]. Furthermore,uL-FABP concentrations were positively correlated with the albumin-to-creatinine ratio and systolic blood pressure in patients with DM [Summary Fisher's Z = 0.58 P<0.00001; Summary Fisher's Z =0.24 P<0.0001, respectively] and negatively correlated with estimated glomerular filtration rate in patients with DM [Summary Fisher's Z = -0.36, P<0.0001]. . CONCLUSION. Urinary L-FABP may be a potential marker for the detection of all stages of DN and for the prediction of the progression and severity of DN in patients with type 1 and 2 DM. Urinary L-FABP was a useful biomarker for the early detection of kidney injury even when urinary albumin levels were in the normal range